Theoretical and applied problems of interaction between the international and national legal systems - O. A. Kiseleva (Правоприменение, 2022)
The subject. The interaction of modern national legal systems and the international legal system is still the most controversial legal phenomenon. An exclusively national approach to solving issues of the general theory of international law could not and cannot justify expectations and close the need for legal comprehension. The situation is aggravated by the fact that, at the level of universal international law, the solution of issues on the agenda with the help of positive methods of legal regulation, and, consequently, the implementation of the norms of existing international treaties today are criticized, tested and often completely violated. The implementation of the norms of existing international treaties is increasingly faced with attempts to refute their postulates using the "customs" under which those "rules" are veiled. In such conditions, national legal systems may experience an increased "feeling of jealousy" to their sovereignty and try to "close" as much as possible using the principle of non-interference in the internal affairs of the state.Purpose of the study. In such conditions, it is most important to choose the right vector in improving international law, and not order, law based on normative principles. It is important to correctly "choose the key" to harmonizing the will of sovereign states of our time. The article is devoted to the search for a more correct way of developing international law through its interaction, and not counteraction with the national one.Methodology. The research was carried out using a formal legal interpretation of international legal acts, as well as a comparative analysis of Russian and foreign legal literature. Structural and systemic methods are also the backbone of the study. The conclusions of the work are based on dialectical unity and the struggle of opposites, as well as on interacting deduction and induction in relation to legal systems.The main results. The growing trend towards fragmentation of international law leads to a reduction in the base of sources in the universal sphere of international law. The intensification of regionalization and the creation of regional unions of sovereign states is becoming a source of polar processes: on the one hand, supranational control over the observance of international law by states within their legal system increases, on the other hand, natural situations of non-execution of decisions of international judicial bodies arise. Such situations, without a proper assessment of the reasons for the issuance of the international acts of law enforcement themselves, can lead to unfounded criticism. There is an impressive amount of work in the field of correlation between international and national law, as well as in the field of enforcement of decisions of international judicial bodies. Despite this, in the field of practical implementation of the norms of international law, there remains a lack of doctrinal developments. Such a situation will inevitably lead to attempts to create a semblance of a norm, an escalation of confrontation, and an inability to reach agreement on issues on the agenda. The situation at the level of the universal international legal system is aggravating, therefore, the verification of the limits of competence of regional education authorities, in particular of supranational judicial control bodies, becomes even more important.Сonclusions. The author comes to the conclusion that, on the one hand, in the sphere of universal international law, there is a reduction in the base of sources of international law. On the other hand, in the field of regional international integration, on the contrary, the number of sources of international legal regulation is increasing, and the process of their implementation is intensifying. Universal international law based on the principles of the UN Charter is the most qualitative regulator of the field of international public relations. However, at the present stage of development of the international community, regional integration may well come to its aid: through regional interaction, the consolidation of the wills of sovereign states can and should be achieved a legal constructive dialogue on key issues of already universal international law. Using the approaches of national legal regulation exclusively and unilaterally, it is impossible to productively approach issues of international law: neither in the field of creating international organizations of various types, nor in matters of fulfilling obligations under international law. According to the results of the study, it was concluded that only non-confrontational interaction of specialists in the field of international and national (primarily constitutional) law can provide the construction of the most effective model of interaction of these legal systems. This requires a transformation of the basic approaches to the issues of interaction between international and national law. The basic unity of the general theory of law and the specific features of legal systems should be the starting points for doctrinal research of existing legal structures and the practice of their implementation.